2010
DOI: 10.1590/s0001-37652010000400026
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and acidity status of latossolos (oxisols) under pasture in the Brazilian Cerrado

Abstract: The Cerrado region, with over 50 million hectares of cultivated pasture, provides 55% of Brazilian beef production. Previous investigations have shown that about 70-80% of this pasture is affected by some kind of degradation, leading to low productivity. However, until now, few surveys have been carried out on a regional scale. The aim of the present work is both to assess the fertility and acidity levels of Cerrado soils under pasture and compare the variability of the soils characteristics on a regional scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
(15 reference statements)
2
16
0
4
Order By: Relevance
“…Cerrado soils are weathered, highly acidic, and contain small amounts of nutrients essential for the cultivation of plants (VENDRAME et al, 2010). In agreement with previous studies, micronutrient defi ciencies in Brazil have been observed more frequently in Cerrado soils (LUCHESE et al, 2004).…”
Section: Introductionsupporting
confidence: 89%
“…Cerrado soils are weathered, highly acidic, and contain small amounts of nutrients essential for the cultivation of plants (VENDRAME et al, 2010). In agreement with previous studies, micronutrient defi ciencies in Brazil have been observed more frequently in Cerrado soils (LUCHESE et al, 2004).…”
Section: Introductionsupporting
confidence: 89%
“…The classification of the soils as Latosols was based on field observations of the presence of a latosolic horizon (resulting from long and intense weathering in which the clay fraction is dominated by low-activity clays, such as kaolinite and (hydr)oxides of Fe and Al) and on some analytical determinations made on the Bw horizons (to determine particle size distribution and the molecular ratio SiO 2 :Al 2 O 3 (Ki): data not shown). Some details regarding soil classification are presented by Vendrame et al (2010).…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
“…Pesquisas recentes indicam que grande parte dessas pastagens apresentam solos com variados graus de degradação, resultando em baixa produtividade, devido principalmente à baixa atividade biológica e defi ciência de macro e micronutrientes nos solos (VENDRAME et al, 2010 Entre as espécies forrageiras utilizadas no Cerrado, está o capim Tifton 85 (Cynodon spp). Essa forrageira possui, como características, hastes de grandes dimensões, que são dotadas de folhas fi nas, de cor verde-escura, e rizomas bem desenvolvidos, além de uma boa relação folha-colmo, conferindolhe um bom valor nutritivo (SOARES FILHO et al, 2002).…”
Section: Introductionunclassified